Investigation and Analysis of Failure Modes in 16A Switches - Sudhakaran, P.; Usha, S. (Journal of Electronics and Informatics, 2022)
This project work deals with the investigating and analysis of failure modes in 16A switch. The objective of this project is to increase the lifespan of the switches and to operate safer in high voltages. Mainly in water heater, due to fluctuation or over loading reasons, heat is produced in the switch terminals, and this causes the failure effects in electric switch components. Therefore, to avoid or reduce the switch internal components failure, this work is carried out. Different approaches are initiated to measure the switch failure reduction effects, such as, analyzing the effects by cooling paint coating used to decrease the heat effect and measuring the temperature reduction value. From the inference of the results, the suggestions to avoid the effects of 16 A switch damages have been provided.
Keywords: Switches; cooling paint; polycarbonate; switch socket